2014
DOI: 10.1017/s1049023x14000235
|View full text |Cite
|
Sign up to set email alerts
|

Education and Training Initiatives for Crisis Management in the European Union: A Web-based Analysis of Available Programs

Abstract: Although ETIs currently exist, they are not broadly available in all 27 EU countries. Also, the curricula do not cover all key elements of disaster management in a standardized and competency-based structure. This study has identified the need to develop a standardized competency-based educational and training program for all European countries that will ensure the practice and policies that meet both the standards of care and the broader expectations for professionalization of the disaster and crisis workforc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
60
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4
1

Relationship

3
7

Authors

Journals

citations
Cited by 74 publications
(76 citation statements)
references
References 14 publications
0
60
0
3
Order By: Relevance
“…Ingrassia and coworkers studied the disaster management educational and training initiatives at the postgraduate level in EU countries and found that face-to-face education was the most common teaching method used. The contents were multi-and cross-disciplinary, and a competency-based approach to curriculum content was present [43]. Bajow introduced a new undergraduate community-based disaster medicine course [38].…”
Section: Discussionmentioning
confidence: 99%
“…Ingrassia and coworkers studied the disaster management educational and training initiatives at the postgraduate level in EU countries and found that face-to-face education was the most common teaching method used. The contents were multi-and cross-disciplinary, and a competency-based approach to curriculum content was present [43]. Bajow introduced a new undergraduate community-based disaster medicine course [38].…”
Section: Discussionmentioning
confidence: 99%
“…However, in the face of large-scale disasters, the personnel trained in disaster medicine can be overwhelmed by the demands of the disaster and other medical personnel have to pitch in. In view of the gaps in undergraduate and postgraduate disaster medicine education, [6][7][8][9][10] some educational authorities have called for improved disaster medicine education [11,12] and several medical schools and professional organizations have developed curricula in disaster medicine for education of all physicians [1][2][3][4][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, the international humanitarian community has been drawing attention to the compelling need for competency-based training curricula based on astandard set of cross-cutting and professionspeci c competencies (4,19).Since young doctors, born in a new era of highly-specialized medicine, have been increasing their presence in international aid projects, good preparation and performance oversight are paramount to guarantee best practice also in resource-strained settings(9).…”
Section: Discussionmentioning
confidence: 99%